Atelier de fotografia : estudo de caso de processos alternativos de produção de imagem no atelier de fotografia analógica - Gandini, Marcelo Mattos (2016)
The case study of analog photography workshop has the objective to investigate the production of photographic images from alternative processes of imaging. The focus of the investigation is the description of the course of this process, from offering an elective course at the Center of Arts University at UFES called "Atelier Analog Photography" for regular students of this institution. The work reflected on imagery creation process through analog photographic procedures from photographic processes such as: negative hand made, palimpsest, Cyanotype quimigrama also highlighting the hybrid constitution of these forms. We studied the production and joints of these images, the written verbal discourse being analyzed produced by producers students and the images and processes grounded in experiences in the photo lab. Support this theoretical research as Vilém Flusser, Walter Benjamin, Roland Barthes and Luiz Guimarães Monforte, who discussed and problematized the photographic image, enabling an understanding of the different ways poetic, conceptual and technical today. To analyze the meanings of images and discourses produced used the theory of meaning and theoretical studies proposed by Algirdas Julien Greimas, Jean Marie Floch, Anamélia Bueno Buoro and Moema Martins Rebolças. We investigate the possibilities of photographic techniques inherent to sensitive and photosensitive surfaces, the photochemical solutions and the crossing of these photographic possibilities with other languages. Eschewing the camera work confronts the images with their specificities and seeks to discover the paths of various production processes for them from unveiling the images produced and speeches